SUPPLETIVISM OF THE LEXICAL PLAN IN THE TURKIC LANGUAGES ( BASED ON THE TERMS OF KINSHIP IN THE UZBEK LANGUAGE) - Vasila Vakhobovna Karimova; Munisa Karimova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with one of the most important problems of the modern science of language, which was not the object of special consideration. This problem is the presence and functioning of suppletivism and lexical suppletives in the language.